PERAN INTERMEDIASI PERBANKAN TERHADAP USAHA MIKRO KECIL DAN MENENGAH (UMKM) - Badriyah, Nurul (Jurnal Ekonomi Pembangunan, 2009)
Bank is a business entity which accummulate funds from society in a form of saving and distributing it to society in a form of credit or other forms available in order to enhance the standard of living of society in general. Bank play role as intermediary institution which bridging two party with different self interest, whether in accumulating or investing, or even in providing other banking services including clearing. SMEs is one of business entity characterized as self liquidating since all of their funding acquired from financial institution is used to finance their business activity. It is different with corporate, where usually funding that is acquired from bank is mostly used for investment or complimenting the fixed capital of company. SMEs is not least important as bigger scale business entity, including in credit distribution since SMEs is proven to have significant and important role in economic development.